Prevalence of metabolic diseases in newborns of the neonatal Intensive Care Unit submitted to the heel prick test (Research, Society and Development, 2021)
Objectives: To describe the prevalence of metabolic diseases in newborns in the neonatal intensive care unit undergoing heel prick testing. Method: This is a cross-sectional, retrospective and analytical study, through the analysis of 261 medical records of newborns of reference maternity in Sergipe with newborns who required hospitalization in a neonatal intensive care unit and who were followed up in the hospital. outpatient clinic of maternity specialties. Results: Of the 261 medical records evaluated, 105 presented results of the heel prick test. Among the diseases screened, it is noted that the dosage of Phenylalanine was within the normal range in all patients; positivity for Congenital Hypothyroidism was 3.8%, for Cystic Fibrosis it was 2%, for Congenital Adrenal Hyperplasia it was 1%, for Biotinidase Deficiency it was 4.2% and for Hemoglobinopathies it was 9.5%. Conclusion: The most prevalent metabolic disease in this study was the group that comprises Hemoglobinopathies screened by the heel prick test, which correspond to 9.5% of positive results. This finding corroborates the profile of the prevalence of metabolic disease in Brazil, with emphasis on sickle cell anemia, in neonatal screening.